Relative abundance, diet and growth of perch (Perca fluviatilis) and roach (Rutilus rutilus) at Tvärminne, northern Baltic Sea, in 1975 and 1997: responses to eutrophication? - Lappalainen, A.; Rask, M.; Koponen, H.; Vesala, S. (Boreal Environment Research Publishing Board, 2024)
The coastal waters of the northern Baltic Sea have been undergoing a progressive process of eutrophication in recent decades. Gill net samples were taken in the Tvärminne area (SW Finland) to assess the effects of coastal eutrophication on the stocks of two common species, perch (Perca fluviatilis) and roach (Rutilus rutilus). The relative abundance, diet and growth of perch were rather similar in 1975 and in 1997. However, the higher abundance of roach catches in the outer archipelago and their slower growth rate indicate that roach stocks have increased during the last 20 years. Perch feed mainly on macro-crustaceans and fish, whereas roach feed mainly on molluscs. In 1997, Saduria entomon was absent from the diet of perch, and the contribution of Mytilus edulis and Cerastoderma glaucum, two important components in the diet of roach, had decreased, possibly reflecting changes in local benthic communities. The most pronounced change, however, was the increase in local roach stocks, which was attributed to coastal eutrophication.